SELECTION OF PROMISING POTATO VARIETY SAMPLES FOR EARLY PLANTING (Modern American Journal of Biological and Environmental Sciences, 2026)
This paper presents the results of evaluating potato (Solanum tuberosum L.) varieties under the agro-climatic conditions of the Tashkent region and selecting promising samples for early planting. The study analyzed phenological and biometric characteristics of 36 potato varieties and breeding lines of both local and foreign origin. The results showed that some varieties emerged 1–3 days earlier than the control, and also exhibited higher growth and development parameters as well as increased yield.In particular, Evolution, Red Bullet, Romantika, Mikado, Arizona, Desirée, Spunta, Gala, Kuroda, Sineglazka, Tashkent early, as well as lines №01, №02, №05, №9, and №12 demonstrated high performance.These varieties and lines were identified as promising for early planting.